2013
DOI: 10.1017/s0007114513000950
|View full text |Cite
|
Sign up to set email alerts
|

Early growth and postprandial appetite regulatory hormone responses

Abstract: Strong epidemiological evidence suggests that slow prenatal or postnatal growth is associated with an increased risk of CVD and other metabolic diseases. However, little is known whether early growth affects postprandial metabolism and, especially, the appetite regulatory hormone system. Therefore, we investigated the impact of early growth on postprandial appetite regulatory hormone responses to two high-protein and two high-fat content meals. Healthy, 65-75-year-old volunteers from the Helsinki Birth Cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In addition, we found that higher levels of PYY were associated with a lower weight for length SDS at 3 months. These results are in line with the data of Helsinki Birth Cohort Study, where they found higher PYY levels in adulthood when the infants had a lower growth rate during infancy [28]. Our study shows that these differences can already be found in early life.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that higher levels of PYY were associated with a lower weight for length SDS at 3 months. These results are in line with the data of Helsinki Birth Cohort Study, where they found higher PYY levels in adulthood when the infants had a lower growth rate during infancy [28]. Our study shows that these differences can already be found in early life.…”
Section: Discussionsupporting
confidence: 93%
“…It inhibits gastric motility; consequently, it increases the efficiency of digestion and nutrient absorption after a meal and increases the absorption of water and electrolytes in the colon. It seems obvious that the concentration of peptide YY, in particular, would have individual and important regulatory mechanisms in the infant who is in a crucial stage of accelerated growth (Breij et al, ; Perälä et al, ). Breij et al () have reported that breastfed infants have higher Peptide YY concentrations, which could be a link to the protective role against obesity in exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, overweight individuals may well experience an enhanced orexigenic drive and a reduced satiety sensation, potentially overwhelming conscious dietary regulation. Human epidemiologic studies, including the Dutch winter famine, confirm the potential for programmed hyperphagia and obesity (Lussana et al, 2008;Perala et al, 2013). The results of the present study provide insight into the neurodevelopmental mechanisms by which this dysfunctional appetite network is formed.…”
Section: Discussionmentioning
confidence: 99%